Study on the overview on foodborne bacteria in food with animal origin in Iran; Part four: Poultry and egg - S.S Shekarforoush; S.M.M Kiaie; G Karim; S.M Razavi Rohani; N Rokni; M Abbasvali (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2013)
In this study, the contamination of poultry meat and eggs to pathogenic bacteria was investigated in Iran, for over three decades. Health assessment of these two products is highly important due to their high level of consumption and consequent health risks of food borne diseases such as salmonellosis. Many reports indicate the presence of majority of pathogenic bacteria such as campylobacter, staphylococci, salmonellas, etc. in the poultry abattoirs across the country. It seems that most of these contaminations had been occurred through cross contamination during slaughtering or other stages of processing. Although many bacterial contaminations have been reported in eggs (e.g., streptococci, staphylococci, or Escherichia coli), most of studies have focused on salmonella as eggs are among the major transmission routes of this bacterium. In several suveys, salmonella has been isolated from the shell of the eggs of native breeds. According to the studies, campylobacter contamination has not been reported. Moreober, occurrence rate with other bacteria species was very low. It seems that due to the high proportions of chicken meat and eggs in the food basket of community, even low levels of contamination could be of great concern. It was concluded that maintaining of hygienic conditions and improving the knowledge of producers in the food production chain could be effective in reducing the overall contamination of pathogenic bacterial.